Impact of Antimicrobial Agents on Bacterial Isolates from Dental Decay - Ali, Muna Jalal; Makky, Essam A.; M. M., Yusoff (Asian Research Publishing Network (ARPN), 2016)
Tooth decay is considered the most widespread infectious disease in the world. This study aims to isolate and identify the important bacteria related to tooth decay, determine the sensitivity of bacteria in certain types of antimicrobial agents, and study the effect of heavy metals and virulence factores on bacterial isolates. A total of 50 swabs were collected from the mouths of patients from both gender, with ages ranging from 1–60 years. Results showed that infection rates in younger age groups (1–20 and 20–40) are higher than the elder group (40–60), with percent incidence of 44% and 32%, respectively.In addition, 100% resistance was recorded against seven heavy metals, including silver nitrate, iron chloride, zinc chloride, and lead acetate. The sensitivity to mercury, cadmium, and copper sulfate were 100%, 86.44%, and 1.69%, respectively. Hemolysin had the highest ability to produce virulence factors (72.88%), followed by lecithinase (42.37%) and protease (25.42%). Lipase and urease had the lowest virulence factor production (10.16%).